Impact of gastrointestinal conditions, restrictive diets and mental health on health-related quality of life: cross-sectional population-based study in Australia. Issue 6 (27th June 2019) - Stocks, Nigel P; Gonzalez-Chica, David; Hay, Phillipa
Abstract : Objectives: To assess the relationship between gastrointestinal conditions, restrictive diets, mental health and health-related quality of life (HRQoL). Design: Cross-sectional population-based face-to-face survey. Setting: South Australia. Participants: A representative sample of 2912 consenting adults (48.9±18.1 years; 50.9% females) investigated in 2015. Primary and secondary outcome measures: Participants self-reported diagnosis of gastrointestinal conditions, mental health and current use of restrictive diets. The physical component score (PCS) and mental component score (MCS) of HRQoL were investigated (Study Short Form 12 V.1 questionnaire). Linear regression models were used to test the associations, adjusting for (1) sociodemographic variables, (2) mental health status and (3) lifestyle and body mass index. Results: The prevalence of restrictive diets (36.1%; 95% CI 33.9 to 38.3) was higher among those with any self-reported gastrointestinal condition (60.7% vs 31.3% for those without these conditions; p<0.001). PCS was lower among those with a gastrointestinal condition (mean difference=−3.4; 95% CI −4.5 to −2.4) or on a restrictive diet (mean difference=−1.9; 95% CI −2.7 to −1.1), with a similar pattern, but with a smaller effect, observed for MCS. Being on a restrictive diet did not modify the relationship between having a gastrointestinal condition and reduced HRQoL. However, having a gastrointestinal condition was associated with a 2.4 points lower PCS (95% CI −3.5 to −1.3) among those without a mental health problem, while for those affected by a mental health condition this reduction was greater (mean difference=−5.9; 95% CI −8.7 to −3.1). For MCS, there was no evidence of interaction between mental health and gastrointestinal conditions. Conclusions: One-third of Australian adults are restricting their diet, and this is associated with lower HRQoL. Being on a restrictive diet was not associated with a better HRQoL among individuals with a gastrointestinal condition. Mental health problems were associated with a stronger adverse relationship between gastrointestinal diseases and physical HRQoL. Health professionals should be alert to these associations when trying to improve health outcomes for patients.